2023
DOI: 10.1088/1367-2630/acc1ff
|View full text |Cite
|
Sign up to set email alerts
|

Effects of strong spin-orbit coupling on Shiba states from magnetic adatoms using first-principles theory

Abstract: Magnetic impurities at surfaces of superconductors can induce bound states referred to as Yu-Shiba-Rusinov states (i.e., Shiba states) within superconducting (SC) gaps. For superconductors with strong spin-orbit coupling (SOC), Shiba states arising from even single magnetic adatoms are too complex to be fully understood using effective models alone because SOC cannot be treated perturbatively and multiple orbitals are strongly mixed with spin projections. Here we investigate Shiba states of single magnetic ada… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 56 publications
0
4
0
Order By: Relevance
“…The introduction of a phase difference moves the energy of the inverted YSR states away from the edge of the minigap, closer to zero energy, and pushes them further toward zero as the phase difference increases. This effect is similar to the shift of single-impurity YSR states with the canting angle of the magnetic moment [27]. This also leaves the remaining YSR states at the minigap edge around the middle of the nanowire noninverted [Fig.…”
Section: Phase Shifts and Topological Fragmentationmentioning
confidence: 69%
See 1 more Smart Citation
“…The introduction of a phase difference moves the energy of the inverted YSR states away from the edge of the minigap, closer to zero energy, and pushes them further toward zero as the phase difference increases. This effect is similar to the shift of single-impurity YSR states with the canting angle of the magnetic moment [27]. This also leaves the remaining YSR states at the minigap edge around the middle of the nanowire noninverted [Fig.…”
Section: Phase Shifts and Topological Fragmentationmentioning
confidence: 69%
“…In Ref. [27] it was shown that a single magnetic impurity can host a 134513-6 zero-energy state by imposing certain canting angles. Here one should remember how Shiba bands are formed.…”
Section: Local Manipulation Of Individual Spins and The Formation Of ...mentioning
confidence: 99%
“…But it has to be emphasized that even though there are states at zero energy at some spiraling angle, this does not necessarily mean that MZMs are found. As has been demonstrated before, even in the case of a single magnetic impurity on the surface of a superconducting host, it is possible to obtain a state at zero energy by imposing a canting angle [62], even though it is not possible to obtain MZMs for a single impurity. Such states are just YSR states that are accidentally shifted to zero energy as a result of the canting angle.…”
Section: Spin Spirals In the Superconducting Statementioning
confidence: 94%
“…This is allowed by the Green's-function-based solution of the Kohn-Sham-Dirac-Bogoliubov-de Gennes (KSDBdG) equations [59,60]. On the one hand, it has been demonstrated previously that many aspects of STM experiments are reproducible by such calculations [60][61][62][63], while on the other hand, it allows us to calculate other quantities, such as spin-polarization and the superconducting order parameter (OP) [64], which are important to understand the nature of these states. Furthermore, some of their properties can be further explored and tested by computational experiments which go beyond the capabilities of conventional experimental techniques.…”
Section: Introductionmentioning
confidence: 99%